Closed-loop identification of an industrial robot containing flexibilities - Östring, Måns; Gunnarsson, Svante; Norrlöf, Mikael (Control engineering practice, 2003)
Closed-loop identification of an industrial robot of the type ABB IRB 1400 is considered. Data are collected when the robot is subject to feedback control and moving around axis one. Both black-box and physically parameterized models are identified. A main purpose is to model the mechanical flexibilities. It is found that a model consisting of three-masses connected by springs and dampers gives a good description of the dynamics of the robot.